A Description of Staff-resident Interactions in Assisted Living. (June 2021) - Paudel, Anju; Galik, Elizabeth; Resnick, Barbara; Doran, Kelly; Boltz, Marie; Zhu, Shijun
Positive social and care interactions are vital to understand and successfully accomplish the daily care needs of the residents in assisted living (AL) and optimize their quality of life. The purpose of this study was to explore and describe the staff-resident interactions in AL. This descriptive analysis utilized baseline data in a randomized trial that included 379 residents from 59 AL facilities. The majority of the interactions observed were positive; almost 25% were neutral or negative. Most interactions were care-related (31.9%) or one-on-one (27.4%), occurred with nursing (40.2%) or support staff (e.g., dining aide; 24.6%), and involved close interpersonal distance (64.6%). Future research should focus on the transition of neutral or negative interactions to positive and explore the factors that might influence neutral and negative interactions. Additionally, innovative approaches are needed to optimize interactions amid physical distancing in the context of the COVID-19 pandemic.